Research note: attitudes of teachers and undergraduate students regarding three augmentative and alternative communication modalities. (1st October 2016) - Schäfer, Martina Christina Marion; Sutherland, Dean; McLay, Laurie; Achmadi, Donna; van der Meer, Larah; Sigafoos, Jeff; Lancioni, Giulio E.; O'Reilly, Mark F.; Schlosser, Ralf W.; Marschik, Peter B.
Abstract: The social validity of different communication modalities is a potentially important variable to consider when designing augmentative and alternative communication (AAC) interventions. To assess the social validity of three AAC modes (i.e., manual signing, picture exchange, and an iPad ® -based speech-generating device), we asked 59 undergraduate students (pre-service teachers) and 43 teachers to watch a video explaining each mode. They were then asked to nominate the mode they perceived to be easiest to learn as well as the most intelligible, effective, and preferred. Participants were also asked to list the main reasons for their nominations and report on their experience with each modality. Most participants (68–86%) nominated the iPad-based speech-generating device (SGD) as easiest to learn, as well as the most intelligible, effective, and preferred. This device was perceived to be easy to understand and use and to have familiar and socially acceptable technology. Results suggest that iPad-based SGDs were perceived as more socially valid among this sample of teachers and undergraduate students. Information of this type may have some relevance to designing AAC supports for people who use AAC and their current and future potential communication partners.